2021
DOI: 10.1002/cbin.11612
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes of the male urogenital system: Interrelationships, possible functions, and pathological implications

Abstract: The male urogenital system is composed of the reproductive system and the urinary tract; they have an interconnected embryonic development and share one of their anatomical components, the urethra. This system has a highly complex physiology deeply interconnected with the circulatory and nervous systems, as well as being capable of adapting to environmental variations; it also undergoes changes with aging and, in the case of the reproductive system, with seasonality.The stroma is an essential component in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 71 publications
2
9
0
1
Order By: Relevance
“…Although currently anomalies in TCs/CD34 + stromal cells have been detected in a number of human pathological tissues, much work has yet to be done to clarify their functional implications [14,23,[25][26][27][28][29][30][31][44][45][46][47][48][49][50][51][52][53][54][55]. For instance, preclinical animal models reproducing tissue alterations of TCs/CD34 + stromal cells, much like those found in human diseases, may clearly represent an invaluable tool for elucidating the effective contribution of these cells to disease pathogenesis and/or pathophysiology, which could often only be supposed [25].…”
Section: Discussionmentioning
confidence: 99%
“…Although currently anomalies in TCs/CD34 + stromal cells have been detected in a number of human pathological tissues, much work has yet to be done to clarify their functional implications [14,23,[25][26][27][28][29][30][31][44][45][46][47][48][49][50][51][52][53][54][55]. For instance, preclinical animal models reproducing tissue alterations of TCs/CD34 + stromal cells, much like those found in human diseases, may clearly represent an invaluable tool for elucidating the effective contribution of these cells to disease pathogenesis and/or pathophysiology, which could often only be supposed [25].…”
Section: Discussionmentioning
confidence: 99%
“…TCs form an intercellular 3D network structure in the intestinal muscular layer that resists deformation and thus supports gastrointestinal peristalsis ( 45 ). Similarly, the network of TCs creating a 3D scaffold in the human urinary bladder interstitial space provides mechanical support during bladder wall expansion and relaxation and avoids abnormal wall deformation ( 46 ). Tubal TCs also produce slow waves in the smooth muscle of the oviduct and are considered pacemaker cells of the oviduct ( 40 , 41 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Telocytes are a new type of classic interstitial cells first described in the early 21 st century (Hinescu and Popescu, 2005) present in several organs, including the human testicle (Marini et al, 2018) and mdx mice testes (Gomes et al, 2021). Although their function has not yet been elucidated, some hypotheses indicate that these cells may be involved in the synthesis of testis lipids in the genital system (Sanches et al, 2021), is due to the communication of cytoplasmic processes through telopods (Tp), with multilamellar bodies (lipid storage) located in the Leydig cell cytoplasm (Haseeb et al, 2019). Furthermore, the presence of testicular telocytes in dystrophic mice seems to imply in spermatogenesis mechanisms, potentially aiding in seminiferous tubuletestosterone uptake (Gomes et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…MLBs have been found near blood vessels or telocyte cells (Haseeb et al, 2019), the latter comprising a new cell found in the peritubular compartment. Although the function of this cell has not yet been elucidated, studies propose their participation in testes lipid synthesis (Sanches et al, 2021).…”
Section: Introductionmentioning
confidence: 99%